How well will Brazil's system of atlantic forest reserves maintain viable bird populations? - Marsden, S. J.; Whiffin, M.; Galetti, M.; Fielding, A. H. (Springer, 2005)
It is crucial for biodiversity conservation that protected areas are large and effective enough to support viable populations of their original species. We used a point count distance sampling method to estimate population sizes of a range of bird species in three Atlantic forest protected areas of size 5600, 22,500, and 46,050 ha. Population sizes were generally related to reserve area, although in the mid-sized reserve, there were many rare species reflecting a high degree of habitat heterogeneity. The proportions of forest species having estimated populations > 500 ranged from 55% of 210 species in the largest reserve to just 25% of 140 species in the smallest reserve. All forest species in the largest reserves had expected populations > 100, but in the small reserve, 28% (38 species) had populations < 100 individuals. Atlantic forest endemics were no more or less likely to have small populations than widespread species. There are 79 reserves (> 1000 ha) in the Atlantic forest lowlands. However, all but three reserves in the north of the region (Espirito Santo and states north) are smaller than 10,000 ha, and we predict serious levels of local extinction from these reserves. Habitat heterogeneity within reserves may promote species richness within them, but it may also be important in determining species loss over time by suppressing populations of individual species. We suggest that most reserves in the region are so small that homogeneity in the habitat/altitude within them is beneficial for maintenance of their (comparatively small) original species compliment. A lack of protection in the north, continued detrimental human activity inside reserves, and our poor knowledge of how well the reserve system protects individual taxa, are crucial considerations in biodiversity management in the region.
Keywords: Atlantic forest; birds; Brazil; distance sampling; extinction; population viability; protected areas